Dynamic Modeling and Nyquist Stability Analysis of a Non-Interacting Two-Tank Series Thermal System - Yogi Yolanda; Yola Bertilsya Hendri; Salma Liska; Lisa Legawati; Suhendri Suhendri; Alltop Amri Ya Habib; Zulfansyah Zulfansyah (Journal of Engineering Science and Technology Management, 2026)
Series tank systems are vital in chemical industries but susceptible to mass and thermal disturbances, making stability analysis essential. This study models the level and temperature dynamics of a non-interacting two-tank system equipped with a heater in Tank-01, analyzing its stability via Nyquist plots. The methodology involves laboratory step-response experiments validated against mathematical models derived using Laplace Transforms and Explicit Euler methods. Results demonstrate the model closely matches experimental data; Tank-01 exhibits first-order characteristics, while Tank-02 functions as a second-order system. The physical system successfully handled +52% and -35% step disturbances within liquid height limits of 3–24 cm and feed flow rates of 40.33–136.5 cm³/s. Furthermore, Nyquist analysis confirms the open-loop thermal process is inherently stable across all tested capacities. Maximum level and thermal process gains were 0.3787 and 0.0062, respectively. Ultimately, this study confirms the non-interacting two-tank system possesses stable, self-regulating characteristics against load disturbances within operational limits.